ANTIMALARIAL AND ANTITUBERCULAR ACTIVITIES OF CRUDE METHANOL EXTRACT AND FRACTIONS OF THE BULB OF CRINUM JAGUS ( Linn.) (2015)
Crinum jagus is a medicinal plant used traditionally to treat tuberculosis, malaria and other bacterial infections. However, there are limited documented scientific studies to substantiate the use of this plant. Due to increase in resistance to malaria and tuberculosis drugs, the need for the development of other drugs is pertinent. This study was designed to determine the pharmacological activities of extract and fractions of Crinum jagus. Methanol extract of C. jagus obtained by soxhlet extraction was subjected to phytochemical analysis and fractionated using column chromatography. Antitubercular and antimicrobial activities of the extract and its fractions were evaluated against isolates of Mycobacterium tuberculosis and selected microorganisms using the disc and agar diffusion methods. Antimalarial activity was assessed in vivo using Rane’s test in Plasmodium berghei infected mice (n = 80 in 10 groups) treated orally with tween 80 (control), 10, 25, 50 and 75 mg/kg of extract and its fractions at 10 mg/kg respectively, while chloroquine (10 mg/kg) and arteether (3 mg/kg) groups served as positive controls. Anti-inflammatory potential was assessed in rats using carrageenan-induced paw inflammatory model. In vitro antioxidant potentials were determined spectrophotometrically using 1,1-diphenyl-2-picryl hydrazyl (DPPH), hydroxyl radical scavenging activities, Total Flavonoids Contents (TFC) and Phenolic Contents (TPC) Antioxidant indices- Superoxide dismutase (SOD) and Catalase (CAT) activities and levels of Malondialdehyde (MDA) and reduced Glutathione (GSH) were determined by spectrophotometry. Aspartate (AST) and Alanine (ALT) amino transferases and Alkaline Phosphatase (ALP) were estimated spectrophotometrically. Data were analysed by Student’s t test at p = 0.05. Phytochemical analysis revealed the presence of alkaloids, flavonoids, phenols and steroids in the crude extract. The extract and its fractions (F1, F2 and F3) showed a concentration- dependent inhibition of Mycobacterium tuberculosis, with F1 having the lowest IC50of : 0.22mg/mL relative to rifampicin (IC50 : 0.19mg/mL) and isoniazid (0.23mg/mL). The extract at 10, 25, 50, 75 mg/kg and F1, F2 and F3 at 10 mg/kg suppressed parasitaemia in Plasmodium berghei infected mice by 70.0, 76.0, 79.0, 87.0% and 89.0, 76.0, 78.0% respectively relative to chloroquine (100%) and arteether (89.0%). The extract at 10, 25, 50, 75 mg/kg and F1, F2 and F3 at 10 mg/kg inhibited oedema in rat paws by 26.0, 30.0, 32.0, 66.0% and 80.0, 25.0, 52.0% UNIVERSITY OF IBADAN LIBRARY iii respectively when compared with indomethacin (95.0%). The extract and its fractions significantly scavenged DPPH and hydroxyl radical in vitro. The TPC and TFC of extract, F1, F2 and F3 at 500 μg/ml were 0.310, 0.460, 0.240, 0.380 μg/mg and 0.523, 0.864, 0.396, 0.643 μg/g respectively. The extract and its fractions significantly reduced MDA level while GSH, SOD and CAT levels were increased. Activities of AST, ALT and ALP were significantly increased at 50 and 75 mg/kg body weight of extract . Crinum jagus exhibited antitubercular, antimalarial and anti-inflammatory activities via scavenging of radicals and antioxidative mechanism. This indicates a promising potential of the plant for drug development. Keywords: Crinum jagus, antituberculosis, antimalarial, antioxidant. Word Count: 471 .